QUALITY OF SERVICE ANALYSIS OF WICO NETWORK GRAPARI TELKOM PURWOKERTO USING TIPHON STANDARD - Hidayat, Rizky Bagas Nur; Oktaviana, Luzi Dwi; Kuncoro, Adam Prayogo (Informatika, Universitas Jenderal Soedirman, 2024)
The main problem of providing internet services for provider companies, especially WiCo GraPARI Telkom Purwokerto in responding to the needs and challenges of technological digitalization. This research aims to analyze the Quality of Service (QoS) of WiCo GraPARI Telkom Purwokerto network using TIPHON standard. The TIPHON standard is a series of standards developed by ETSI (European Telecommunications Standards Institute) in order to support the interoperability of Internet Protocol (IP) based telecommunications services. Testing of throughput, delay, packet loss, and jitter parameters was carried out using the Wireshark application. Testing quality of service parameters is done through four scenarios in quiet and crowded internet network conditions for the process of downloading and uploading videos from Google Drive. The results show that the overall network performance falls into the